1993
DOI: 10.1037/0022-3514.64.5.723
|View full text |Cite
|
Sign up to set email alerts
|

Affect, cognition, and awareness: Affective priming with optimal and suboptimal stimulus exposures.

Abstract: The affective primacy hypothesis (R. B. Zajonc, 1980) asserts that positive and negative affective reactions can be evoked with minimal stimulus input and virtually no cognitive processing. The present work tested this hypothesis by comparing the effects of affective and cognitive priming under extremely brief (suboptimal) and longer (optimal) exposure durations. At suboptimal exposures only affective primes produced significant shifts in Ss' judgments of novel stimuli. These results suggest that when affect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

92
1,091
18
20

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,207 publications
(1,246 citation statements)
references
References 63 publications
92
1,091
18
20
Order By: Relevance
“…Behavioral findings further suggest that emotional stimuli can influence performance on certain tasks even when participants are not consciously aware of the stimuli. Studies using subliminal priming have shown that reaction time is faster when the prime and target are congruent in valence (Bargh et al, 1992) and similarly, subliminal priming effects have been reported with novel, nonrepresentational stimuli presented as targets (Murphy & Zajonc, 1993;Wong & Root, 2003). Importantly, under conditions of restricted attentional resources, emotional stimuli are able to reach conscious awareness even when neutral stimuli cannot (Anderson, 2005;Milders et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Behavioral findings further suggest that emotional stimuli can influence performance on certain tasks even when participants are not consciously aware of the stimuli. Studies using subliminal priming have shown that reaction time is faster when the prime and target are congruent in valence (Bargh et al, 1992) and similarly, subliminal priming effects have been reported with novel, nonrepresentational stimuli presented as targets (Murphy & Zajonc, 1993;Wong & Root, 2003). Importantly, under conditions of restricted attentional resources, emotional stimuli are able to reach conscious awareness even when neutral stimuli cannot (Anderson, 2005;Milders et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…For instance, in nearly every study to date, researchers have relied on an Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998), Extrinsic Affective Simon Task (EAST;De Houwer, 2003) or an affective priming task (AP; Murphy & Zajonc, 1993) to measure automatic foodrelated cognition. Although IAT, EAST and AP effects indicate the extent to which one set of concepts (e.g., 'unhealthy foods' and 'healthy foods') are related to a second set of concepts (e.g., good or bad adjectives), they do not provide any information about the specific manner in which those concepts are related.…”
Section: The Current Researchmentioning
confidence: 99%
“…There is much evidence that facial expressions can be detected pre-consciously and can influence psychophysiological and behavioural responses without awareness of the particular expression (e.g., Dimberg & Ohman, 1996;Dimberg, Thunberg, & Elmehed, 2000;Johnsen & Hugdahl, 1991Mogg & Bradley, 1999;Murphy & Zajonc, 1993;Niedenthal, 1990;Ohman, Esteves, & Soares, 1995;Robinson, 1998;Saban & Hugdahl, 1999;Whalen et al, 1998;Wong, Shevrin, & Williams, 1994). All of these studies presented masked faces for very brief exposure duration (target-to-mask stimulus onset asynchrony [SOA] of less than 35 ms).…”
Section: Introductionmentioning
confidence: 99%